Peran Vitamin D Terhadap Kanker: Sebuah Tinjauan Literatur - Umami, Zahra; Suharjono, Suharjono (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Vitamin D is a potent steroid hormone precursor that regulates a broad spectrum of physiological processes in the body. Besides its general role in bone metabolism, vitamin D plays an important role in the prevention and treatment of many diseases such as cancer. The aim of this literature review is to examine in more depth the role of vitamin D as an anticancer. There are studies that reveal biological mechanisms mediated by vitamin D in regulating cancer cells, such as cell renewal, cell proliferation, cell differentiation, cell transformation, and cell death. Other studies have also revealed a link between the immune system and the anti-neoplastic effects of vitamin D. Research shows that low levels of vitamin D in circulation are associated with an increased risk of cancer. The use of supplementation alone or in combination with immunotherapy or other chemotherapy may promote better clinical outcomes. These promising results still require further development and research through novel approaches targeting vitamin D signaling and metabolic systems to improve cancer therapeutic outcomes.